Early postnatal changes in thyroid-stimulating hormone and subsequent neurodevelopment in preterm infants - Yoo, Myoung-Jin; Jang, Yong Hun; Lee, Gang-Yi; Kang, Habyeong; Ye, Dong Hye; Hwang, Woochang; Yang, Seung; Lee, Hyun Ju (Frontiers in Endocrinology, 2026)
IntroductionThyroid hormones are crucial for brain maturation during late gestation and early infancy. In preterm infants, immaturity of the hypothalamic–pituitary–thyroid axis often leads to transient or delayed dysfunctions undetected by standard newborn screening. As these atypical thyroid patterns have been associated with neurodevelopmental outcomes, serial assessments are warranted to better characterize risk. This study investigated whether thyroid trajectories between birth and discharge predict neurodevelopment at two years and their neural correlates on diffusion tensor imaging (DTI).MethodsThis prospective cohort study included 222 preterm infants born at ≤32 weeks of gestation who underwent serial thyroid function tests at 1–2 weeks and at term-equivalent age or hospital discharge. Thyroid status was classified into quartile-based groups at each time point, and neurodevelopment at two years of corrected age was assessed using the BSID-III. Neurodevelopmental impairment (NDI) was defined as the presence of cerebral palsy, blindness, hearing loss, or a BSID-III cognitive or motor composite score below 85. Diffusion-tensor imaging at term-equivalent age was analyzed to examine brain network properties. Associations between longitudinal TSH quartile patterns and NDI were evaluated using logistic regression, with inverse probability of treatment weighting applied to adjust for baseline differences.ResultsInfants with NDI had significantly higher thyroid-stimulating hormone (TSH) at birth and peak levels during hospitalization compared with typical development (P = 0.017 and P < 0.002). Cross-sectional analyses of TSH quartiles at newborn or TEA/discharge did not reveal independent associations with NDI after adjustment. In contrast, paired trajectories were more informative: infants with persistently low TSH, or those whose values declined from the interquartile to the lowest quartile by TEA/discharge, had a markedly lower risk of NDI (OR 0.24, P = 0.020; OR 0.23, P = 0.035). Brain DTI analyses suggested altered network centrality in the anterior cingulate and superior frontal gyri among infants with higher neonatal TSH.ConclusionPreterm infants with persistently low or decreasing TSH trajectories showed reduced odds of neurodevelopmental impairment. In contrast, persistently high or increasing TSH levels may instead reflect alternative patterns of postnatal HPT-axis adaptation. Corresponding group differences in fronto-limbic regions at discharge provide neurobiological support that altered thyroid function may contribute to atypical brain connectivity underlying later neurodevelopmental outcomes.